2005
DOI: 10.4269/ajtmh.2005.73.392
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Surveillance for Acute Febrile Illness in Egypt: A Focus on Community-Acquired Bloodstream Infections

Abstract: Acute febrile illness (AFI) is a common syndrome in Egypt. However its etiologies are not well characterized. To determine the relative frequency of pathogen etiologies and possibly improve diagnostic, clinical management and public health measures, we implemented laboratory-based surveillance in a network of infectious disease hospitals throughout Egypt. Admitted patients with AFI provided background details and a blood sample for bacterial culture and serologic analysis. Case definitions were based on labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 19 publications
6
72
0
1
Order By: Relevance
“…This result is in agreement with the study done by Afifi et al [28] in Egypt. However, another study by Sherif et al [31] reported an incidence rate of 3.5% among Egyptian women.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result is in agreement with the study done by Afifi et al [28] in Egypt. However, another study by Sherif et al [31] reported an incidence rate of 3.5% among Egyptian women.…”
Section: Discussionsupporting
confidence: 83%
“…It is a major health problem throughout the Middle East, including in Egypt. The identification of risky patients with acute disease is challenging due to the diverse clinical presentations and the need of a specialized laboratory for confirming the diagnosis [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typhi and Brucella spp were the most common infective agents of acute febrile illness. Particularly S. Typhi was detected in blood samples from 5% of the patients under study [20].…”
Section: Egyptmentioning
confidence: 99%
“…A cross sectional comparative study performed in Egypt detected marked discrepancies among antigens from four different locally available sources at three different cut-off values, when sensitivity and specificity were compared [69]. These discrepancies among different brands were supported by different studies [70,71]. In addition, a semi-quantitative slide agglutination and single-tube Widal test was performed poorly in two sub-Saharan African cites [29].…”
Section: Limitations Of Widal Testmentioning
confidence: 99%